HUBUNGAN SINERGIS ANTARA KOMITE MADRASAH DENGAN KEPALA MADRASAH UNTUK MENINGKATKAN KUALITAS SARANA PRASARANA PEMBELAJARAN DI MTS. MADINATUSSALAM PERCUT.SEI TUAN 3 MEDAN - Murimah Syahfitri Nasution; Nuruka Khalila Daulay; Inom Nasution (Universitas Islam Negeri Sumatera Utara Medan, 2021)
The purpose of this research is to get an overview of programs and activities to improve the quality of facilities and infrastructure in MTs. Madinatussalam percut sei sir, synergistic relationship between the committee and the head of MTs. Madinatussalam percut sei sir, factors influencing the role of the madrasa committee create a synergistic relationship between the committee and the head of MTs. Madinatussalam, efforts are being made to ensure the synergy between the committee and madrasah heads in improving the quality of infrastructure in MTs. madinatussalam. The research used in this thesis is qualitative, and the type of descriptive research uses a naturalistic approach. The research subject is the head of the madrasa, madrasa committee, and infrastructure. The data collection techniques used were observation, interviews, and documentation. Data analysis techniques used from Miles and Hurman are data reduction, data presentation and conclusion drawing. And the data validity test was carried out with credibility including triangulation, transferability, dependability and confirmability. The results of this study indicate that, the synergistic relationship that occurs between the committee and the head of the madrasa is well established, the head of the madrasa always involves the committee in planning, implementing, monitoring and evaluating every madrasa agenda as well as the madrasa committee supporting every activity and program organized by the madrasa such as short, medium and long term work programs. Factors influencing The role of the committee in creating a synergistic relationship with the existence of school activities and programs, extracurricular and committee meetings. Efforts are made so that synergy is well established, namely coordination and communication with the community. The conclusion of the research is the activities carried out by the madrasa committee with the madrasa head in improving the quality of learning infrastructure at MTS. Madinatusslam, namely collaborating and deliberation, assisting in raising funds and building madrasas with the necessary needs such as encouraging the procurement of textbooks, improving class facilities, suggestion boxes to accommodate complaints from parents / guardians of students, procurement of extracurricular activities.. Keywords:Synergistic Relationships, Madrasa Committees, Madrasa Heads, Learning Facilities